Speed of capillary blood flow and d-dimer levels in sickle cell anaemia patients in Calabar, cross river state - Effiong, Ofonime Lawrence; Aneke, John C.; Okafor, Ifeyinwa Maryann; Soronnadi, Clara Ngozi; Abasibom, Iniobong Eno (International Journal of Research in Medical Sciences, 2021)
Background: The experience of painful episodes of ill health caused by sequelae of erythrocytes sickling, impaired blood flow, hypercoagulation and vaso-occlusion is one of the hallmarks of sickle cell disease. Preventing painful episodes and promoting the physical wellbeing of persons with sickle cell disease is usually a major objective in the management of the condition. The purpose of this study is to investigate capillary blood flow and D-Dimer activities in people with sickle cell anaemia. Methods: A total of 90 subjects (27 males and 63 females) participated in the study, the study comprised of 34 HbSS patients, three were in crisis and thirty-one in steady state, 9 sickle cell carriers (HbAS) and 47 HbAA were control subjects. The haemoglobin phenotype was determined using haemoglobin electrophoresis at alkaline pH (8.6), speed of capillary blood flow was estimated using vascular Doppler ultrasonographic technique and D-Dimer was determined using ELISA method. Results: Results obtained showed that there was a significant variation (p=0.042) in the mean levels D-Dimer among the groups. There was however no significant variations (p>0.05) in the other parameters among the groups. A post hoc analysis of mean D-Dimer in sickle cell patients, sickle cell carriers and controls showed that the sickle cell patients had significantly higher D-Dimer levels compared with controls. Conclusions: Sickle cells patients in steady state had higher D-Dimer levels compared with controls and sickle cell patients in crisis had lower speed of capillary blood flow when compared to sickle cell patients in steady state and controls.